MODERN METHOD IN FOREIGN LANGUAGE (E Global Congress, 2023)
Changes in education, occurring under the influence of the rapid introduction of information technology in all spheres of life, impose serious requirements on the level of competence of a teacher who needs to master the role of a consultant for a student. Researchers and educators from around the world emphasize the special need for media education.